Genetic engineering approach using early Vinca alkaloid biosynthesis genes led to increased tryptamine and terpenoid indole alkaloids biosynthesis in differentiating cultures of catharanthus roseus - Sharma, A.; Verma, P.; Mathur, A.; Mathur, A.K. (Protoplasma, 2018)
Catharanthus roseus today occupies the central position in ongoing metabolic engineering efforts in medicinal plants. The entire multi-step biogenetic pathway of its very expensive anticancerous alkaloids vinblastine and vincristine is fairly very well dissected at biochemical and gene levels except the pathway steps leading to biosynthesis of monomeric alkaloid catharanthine and tabersonine. In order to enhance the plant-based productivity of these pharma molecules for the drug industry, cell and tissue cultures of C. roseus are being increasingly tested to provide their alternate production platforms. However, a rigid developmental regulation and involvement of different cell, tissues, and organelles in the synthesis of these alkaloids have restricted the utility of these cultures. Therefore, the present study was carried out with pushing the terpenoid indole alkaloid pathway metabolic flux towards dimeric alkaloids vinblastine and vincristine production by over-expressing the two upstream pathway genes tryptophan decarboxylase and strictosidine synthase at two different levels of cellular organization viz. callus and leaf tissues. The transformation experiments were carried out using Agrobacterium tumefaciens LBA1119 strain having tryptophan decarboxylase and strictosidine synthase gene cassette. The callus transformation reported a maximum of 0.027% dry wt vindoline and 0.053% dry wt catharanthine production, whereas, the transiently transformed leaves reported a maximum of 0.30% dry wt vindoline, 0.10% catharanthine, and 0.0027% dry wt vinblastine content. © 2017 Springer-Verlag GmbH Austria
Keywords: Agroinfiltration; Strictosidine Synthase (CrSTR); Terpenoid Indole Alkaloids (TIAs)